PENERAPAN SISTEM INFORMASI AKUNTANSI DENGAN MENGGUNAKAN JARINGAN INFORMASI BERSAMA ANTAR SEKOLAH BERDASARKAN PSAK NO. 45 (Studi Kasus pada Yayasan Nur Hidayah Surakarta) - Munawir, Dewi Saptantinah Puji Astuti & Muhammad Rofiq Sunarko (Universitas Slamet Riyadi, 2017)
The purpose of this study is to describe the application of accountinginformation system by using JIBAS based on PSAK No. 45 on the Foundation ofNur Hidayah Surakarta and describe the constraints in the implementation ofaccounting information system by using JIBAS based on PSAK No.45 on theFoundation of Nur Hidayah Surakarta. This research method using case studyon Foundation of Nur Hidayah Surakarta. The data type used is qualitative dataand quantitative. Data source using primary data and secondary data. Using datacollection techniques interviews and documentation. Data analysis techniques usingdescriptive analysis. Based on the research results obtained the conclusion thatthe application of the accounting information system by using JIBAS basedon PSAK No 45 on the foundation of Nur Hidayah Surakarta done by filling theentire transaction of cash receipts and accounts payable applications JIBAS. Inthe application of the system of internal control on the programs implemented withJIBAS all documents printed manual for further authorization is performed by thecompetent authority, so that it can prevent confusion and manipulation of the databy admin JIBAS. Constraints in the implementation of accounting informationsystem by using JIBAS based on PSAK No. 45 on the Foundation of Nur HidayahSurakarta, namely the lack of training in the use of the Program JIBAS, lack ofcompetence of human resources (HR) and the existence of linkages with FinancialApplications JIBAS Academic.Keyword: application of accounting information systems, financial systems, JIBASinternal control.